Immanuel Kant’s Deontological Ethics and the Moral Legitimacy of Artificial Intelligence in Nigeria’s Healthcare Delivery System - Christian Oruama Keremah; Ebikisei Stanley Udisi (Pinisi Journal of Social Science, 2025)
This study aims to determine the effect of employee competence on service quality at the Donri-Donri sub-district office, Soppeng Regency. By using a quantitative design approach. This type of research is descriptive quantitative using observation techniques, questionnaires, interviews, and documentation in data collection. The study population consisted of 34 people with a population sample using descriptive statistical data analysis techniques and inferential statistics. The results showed that there was a significant and positive influence on the quality of public services in Donri-Donri District, Soppeng Regency. The findings of this study provide an overview of basically knowledge skills and skill abilities that are needed by every sub-district employee so that each task can be carried out quickly and more easily. Various efforts have been made by the government of the Donri-Donri sub-district to maintain the competence of its apparatus through educational and training activities whose aim is to keep employees up to date with information that develops with the alignment of tasks and functions as well as demands for service needs by the community